PENGARUH BRAND AMBASSADOR DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN SCARLETT WHITENING - Santa Monica Ginting; Indra Siregar (Bisnis-Net, 2023)
This research was conducted because of the phenomenon that Scarlett Whitening is the best-selling top brand body lotion and uses marketing techniques such as brand ambassadors and social media marketing, so this study aims to determine the effect of brand ambassadors and social media marketing on purchasing decisions for Scarlett Whitening skincare products. The type of research used in this research is quantitative. The population used in this study were students from several campuses in the city of Medan. The number of respondents consisted of 100 people, using nonprobability sampling technique and determining the sample using purposive sampling. The results of the study show that brand ambassadors and social media marketing have a positive and significant effect on the purchase decision of Scarlett Whitening, either partially or simultaneously. The results of the research on the R Square value show that the brand ambassador and social media marketing variables explain the effect of purchasing decisions by 75.5%, while the remaining 24.5% is explained by other unknown variables in this study.